(untitled) (Homoeopathy for All, 2023)
Seasonal influenza is an acute respiratory infection caused by influenza viruses which circulate in all parts of the world. It represents a year-round disease burden. However, influenza can cause severe illness or death, particularly among high risk groups including the very young, the elderly, pregnant women, health workers and those with serious medical conditions. This article provides an overview of the aetiology, diagnosis, and appropriate general & homoeopathic management of Seasonal flu.